THE ROLE OF JOINT STOCK COMPANY IN CIVIL SOCIETY - Sharipov Asror Safar ugli (Journals Park Publishing, 2024)
In the article, the author examines the regulatory framework governing the status of joint-stock companies, a joint-stock company is considered as a subject of civil law. The instability of the legislation on joint-stock companies is noted.
Keywords: legal entity, joint-stock company, commercial organization, business entity, public joint-stock company.